1983
DOI: 10.1523/jneurosci.03-09-01868.1983
|View full text |Cite
|
Sign up to set email alerts
|

Glutamic acid decarboxylase-immunoreactive neurons and horseradish peroxidase-labeled projection neurons in the ventral posterior nucleus of the cat and Galago senegalensis

Abstract: Immunocytochemical methods were used to identify neurons in the ventral posterior nucleus of the cat and Galago senegalensis that contain glutamic acid decarboxylase (GAD), the synthetic enzyme for the inhibitory neurotransmitter, GABA. In both species GAD-immunoreactive neurons make up about 30% of the total neurons in the ventral posterior nucleus and form a distinct class of small cells. After cortical injections of horseradish peroxidase (HRP), GAD-immunoreactive cells are not labeled with HRP and may, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(34 citation statements)
references
References 44 publications
3
31
0
Order By: Relevance
“…It was higher than the tissue average and higher than that over PSDs, but lower than that found over CTT, RL, and RS terminals. Probably, most of the neurons selected for analysis are thalamocortical projection neurons, as GABAergic local circuit neurons in the VPL generally are smaller than the neurons analyzed in the present study (Penny et al, 1983;Spreafico et al, 1983). Glu-LI has also previously been detected in GAD-negative VPL neurons in the cat by preembedding immunohistochemistry .…”
Section: General Comments On Glutamate Immunohistochemistrymentioning
confidence: 60%
See 1 more Smart Citation
“…It was higher than the tissue average and higher than that over PSDs, but lower than that found over CTT, RL, and RS terminals. Probably, most of the neurons selected for analysis are thalamocortical projection neurons, as GABAergic local circuit neurons in the VPL generally are smaller than the neurons analyzed in the present study (Penny et al, 1983;Spreafico et al, 1983). Glu-LI has also previously been detected in GAD-negative VPL neurons in the cat by preembedding immunohistochemistry .…”
Section: General Comments On Glutamate Immunohistochemistrymentioning
confidence: 60%
“…termiials, whose appearancecorresponds to tet%inals of cortical origin (Jones, 1985;; (3) PSDS (presynaptic dendrites), vesiclecontaining dendritic appendages or dendritic truncs of GABAergic local circuit neuron origin (Penny et al, 1983;Spreafico et al, 1983;Ralston et al, 1988). For each type, the density of gold particles was calculated for eight profiles in each section.…”
Section: Methodsmentioning
confidence: 99%
“…The GABAergic control of thalamocortical neurons is via local interneurons and the cells of the thalamic reticular nucleus (TRN) [2][3][4][5][6][7][8] . Earlier studies have shown that in some mammals GABAergic interneurons are absent or only sparse in many thalamic nuclei.…”
Section: Introductionmentioning
confidence: 99%
“…The lateral geniculate nucleus possesses around 20% of inhibitory interneurons in all species (Barbaresi et al 1986; Benson et al 1992). The somatosensory thalamus and the auditory thalamus possess 20 -25% of inhibitory interneurons in primate and cat (Benson et al 1991; Fitzpatrick et al 1984;Montero 1989;Penny et al 1983; Spreafrico et al 1983) but Ͻ1% in rat Larue 1988, 1996). In the auditory thalamus (medial geniculate nucleus, MG) of rat and cat, an additional source of GABAergic inhibition is directly provided by the sensory inputs coming from the inferior colliculus (Peruzzi et al 1997;Saint Marie et al 1997;.…”
mentioning
confidence: 99%